Auxin Efflux Carrier ZmPGP1 Mediates Root Growth Inhibition under Aluminum Stress. Issue 2 (2nd May 2018) - Zhang, Maolin; Lu, Xiaoduo; Li, Cuiling; Zhang, Bing; Zhang, Chunyi; Zhang, Xian-sheng; Ding, Zhaojun
Abstract : ZmPGP1 controls local auxin accumulation in root tips and regulates root growth under Al stress in maize. Abstract: Auxin has been shown to enhance root growth inhibition under aluminum (Al) stress in Arabidopsis ( Arabidopsis thaliana ). However, in maize ( Zea mays ), auxin may play a negative role in the Al-induced inhibition of root growth. In this study, we identified mutants deficient in the maize auxin efflux carrier P-glycoprotein (ZmPGP1) after ethyl methanesulfonate mutagenesis and used them to elucidate the contribution of ZmPGP1 to Al-induced root growth inhibition. Root growth in the zmpgp1 mutant, which forms shortened roots and is hyposensitive to auxin, was less inhibited by Al stress than that in the inbred line B73. In the zmpgp1 mutants, the root tips displayed higher auxin accumulation and enhanced auxin signaling under Al stress, which was also consistent with the increased expression of auxin-responsive genes. Based on the behavior of the auxin-responsive marker transgene, DR5rev:RFP, we concluded that Al stress reduced the level of auxin in the root tip, which contrasts with the tendency of Al stress-induced Arabidopsis plants to accumulate more auxin in their root tips. In addition, Al stress induced the expression of ZmPGP1 . Therefore, in maize, Al stress is associated with reduced auxin accumulation in root tips, a process that is regulated by ZmPGP1 and thus causes inhibition of root growth. This study provides further evidence about the role of auxin and auxin polar transport in Al-induced root growth regulation in maize.